ODR: an Islamic jurisprudence perspective - Omoola, Sodiq (Accent Publishers, 2019)
Modern Dispute resolution mechanisms have been positively influenced by the advent of the internet. Through Online Dispute Resolution (ODR), several ADR mechanisms have been adapted to small claims, online and cross-border financial transactions. Existing ODR mechanisms seem to ignore certain underpinnings of Islamic jurisprudence in the development.This has made dispute resolution automation unattractive to shariah complaint sectors. Therefore, this paper seeks to examine the relevance of ODR under Islamic jurisprudence. The paper adopts a doctrinal method to expound principles of Islamic jurisprudence (usul-ul-fiqh)which supports new ways of resolving disputes using the internet. The study finds that existing Islamic law ethos such as: sulh, maslahah, sad-ul-dhariah among others are in agreement with the modern realities of online dispute resolution.